Biological Durability of Oil Heat Treated Alder Wood - Robert Lacić (University of Zagreb, Faculty of Forestry and Wood Technology, 2014)
The article presents preliminary results of the biological durability of oil heat treated (OHT) alder wood (Alnus glutinosa) against pure cultures of rot fungi (Postia placenta and Trametes versicolor) in lab conditions. The modification was performed by heating of specimens immersed in soya oil. There were four heating regimes of different duration (6 and 10 hours) at final temperature of 180 and 200 ºC. The increase in mass (MI) caused by modification and mass loss of wood caused by fungal decay (ML) were determined. In addition, the natural durability of alder wood was determined and compared to the natural durability of beech wood as the reference wood species. After modification of alder wood at 200 °C, MI was lower than after treatment at 180 °C. MI was also lower after 10 hours of treatment than after 6 hours of treatment. The results showed significantly increased biological durability of modified alder wood against both tested fungi. The effect of OHT on increasing the biological durability of alder wood was higher against the fungus P. placenta. It seems that the fungus T. versicolor favours the remained oil after modification causing higher mass loss. The results showed that alder wood, thermally modified in soya oil by testing regimens, is not suitable for applications in use classes 3-5.